Skill mismatch and returns to education in manufacturing: A case of India's textile and clothing industry - Prateek Kukreja (Indian Council for Research on International Economic Relations (ICRIER), 2018)
Today, as India treads the path of becoming a knowledge economy, we face a paradox of intensifying skill shortages coupled with unemployment or underemployment among highly educated workers. While a shortage of skills (or under-education) is definitely a cause of concern, surplus education (or over-education) can also lead to underutilization of skills and further lower demand for low skill workers. Given this scenario, the paper attempts to measure the incidence and extent of skill/education mismatch and analyse the economic returns/cost to over/under education in one of India's largest labour intensive industries: Textiles and Clothing (T&C). The study is based on the 68th round of NSS Employment and Unemployment Survey estimates. Using the over-education/required education/undereducation (ORU) models on a cross section dataset of individuals employed (as a regular salaried/ wage employee or as casual wage labour) in India's T&C industry, we find that the overall educational mismatch ratio during 2011-12 was to the tune of 67.61%. Further, results indicate that while returns to surplus education is positive, it is less in magnitude as compared to returns to required education, suggesting underutilization of excess education. There's also a significant wage penalty associated with each deficit year of education.
Keywords: J20; J24; P36; M53; 330; Skill mismatch; textiles; clothing; over-education; required education; undereducation